Calculation of XAFS Cumulants for FCC Crystals Containing Impurity Atom - Nguyen, Van Hung (H. : ĐHQGHN, 2017)
A new procedure for calculation and evaluation of XAFS cumulants of fee crystals containing impurity atom has been developed based on the quantum statistical theory with correlated Einstein model. Analytical expressions for the effective local force constants, correlated Einstein frequency and temperature, first cumulant or net thermal expansion, second cumulant or Debye Waller factor and third cumulant of fee crystals containing impurity atom have been derived. Morse potential parameters of pure crystals and those with impurity included in the derived expressions have been calculated. Numerical results for Cu. Ni. Ni-Cu are found to be in good agreement with experiment